Pendidikan Islam Multikultural di Pondok Pesantren Ulumul Qur’an Stabat Kab. Langkat - Nurhaliza, Siti; Siregar, Ihsan Sufika (Fitrah: Journal of Islamic Education, 2020)
Multiculturalism is a culture or perspective and lifestyle in society. Where in there are various cultural differences, race, religion, gender, ethnicity, language and others. This research is supported by students who have multiculturalism studies. Which is a tribe, suk and culture. Therefore multiculturalism education in the ulumul Qur’an Islamic boarding school in Langkdat is able to provide and carry out multiculturalism education in it which is not in accordance with one another. With the aim of building peace with one another. And to get to know each other the various cultures of each individual, also the creation of good communication between one another. This research is a study using historical research methods and research through one of the alumni of the pesantren Ulumul Qur'an. the results or research findings are the ulumul qura'an pesantren has carried out the multicultural education process. This multicultural education includes the boarding school curriculum implicitly. Which in no way distinguishes between students with one another with a variety of cultures that have.